Report on Proceedings of the Eleventh Annual European CME Forum, King's Fund, London, November 2018. Issue 1 (1st January 2019) - Murray, Ron
ABSTRACT: The historic King's Fund complex in central London was the venue for the Eleventh Annual European CME Forum (11ECF) held 7–9 November 2018. The diverse group of international participants engaged in lively discussion during presentations, workshops, poster displays, a panel discussion and an interactive session with an eloquent local learner. This year's workshop themes considered the CME acronym as a representation of a C hange M anagement E ngine. Each workshop developed these themes by providing practical examples and discussion points for the various stakeholder groups in attendance. Presenters from around the world covered a wide range of topical issues including outcomes planning and evaluation, CPD for CME professionals, collaboration, independence and commercial support, the patient voice, publishing in CME, and CME as a driver of behavioural change. Participants' level of engagement was deemed to be very high, leading to a consensus that the Forum's second decade has started with a bold commitment to further collegiality among providers to foster collaboration in providing high-quality independent CME/CPD in Europe and beyond.